Anelasticity and Lateral Heterogeneities in Earth's Upper Mantle: Impact on Surface Displacements, Self-Attraction and Loading, and Ocean Tide Dynamics - Huang, Pingping; Sulzbach, Roman Lucas; Tanaka, Yoshiyuki; Klemann, Volker; Dobslaw, Henryk; Martinec, Zdeněk; Thomas, Maik (2021)
Surface displacement and self-attraction and loading (SAL) elevation induced by ocean tides are known to be affected by material properties of the solid Earth. Recent studies have shown that, in addition to elasticity, anelasticity considerably impacts surface displacements due to ocean tide loading (OTL). We employ consistent 3D seismic elastic and attenuation tomography models to construct 3D elastic and anelastic earth models, and derive corresponding averaged 1D elastic/anelastic models. We apply these models to systematically study the impact of anelasticity and lateral heterogeneity on M2 OTL displacements and SAL elevation. We find that neglecting lateral heterogeneities highly underestimates displacements and SAL elevation in mid-ocean-ridge regions and in some coastal areas of North and Central America. In comparison to PREM, 3D anelastic models can increase the predicted amplitudes of the vertical displacement and SAL elevation by up to 1.5 mm. The increased amplitudes reduce the discrepancy between GPS-observed OTL displacements and their predictions based on PREM in places like Cornwall (England), Brittany (France), and the Ryukyu Islands (Japan). Applying our results to ocean tides, we discover that the impact on ocean tide dynamics exceeds the predicted SAL elevation correction with an RMS of about 1 mm, reaching an RMS of more than 5 mm in areas like North Atlantic or East Pacific. Due to the fact that such a value reaches the accuracy of modern data-constrained tidal models, we regard the impact of anelastic shear relaxation as significant in tidal modeling.